KEWENANGAN MAHKAMAH KONSTITUSI MENGUJI UU DAN PERLINDUNGAN HAK ASASI MANUSIA - -, Widiastuti (Universitas Slamet Riyadi, 2008)
Abstract : The increasing number of judicial review cases on acts/ordinances demanded by the public to the Court of Constitution has indicated an unsatisfactory attitude concerning the contents of the acts/ordinances as they are in conflict with their rights. Several decision of the Court of Constitution accepted the judicial review claimed by the public by abrogating article(s) or part of the act/ordinance could be seen as a category of the Court of Constitution’s authority to protect human rights. Nevertheless, in practice such a decision of the Court of Constitution cannot be implemented at once since law itself is a system. Key words : Court of Constitution. Human rights.